Enhancement of α-Glucosidase Inhibitory Activity, Antioxidant Activity, and Antioxidant Compounds in Mulberry Leaves Under Salinity Stress - Wulandari, Yasinta Ratna Esti; Sulistyaningsih, Yohana Caecilia; Suprayogi, Agik; Rahminiwati, Min; Triadiati, Triadiati (Bogor Agricultural University, Indonesia, 2026)
Salinity stress disrupts redox homeostasis in plants, leading to notable changes in the levels of bioactive compounds. These compounds are recognized for their significant role in inhibiting the α-glucosidase enzyme, which is relevant in glycemic control. Detailed insights into how salinity stress modulates α-glucosidase inhibition in mulberry leaves remain scarce. This study aims to investigate the effects of salinity stress on α-glucosidase inhibitory activity in mulberry leaf extracts, and to identify accessions exhibiting the most potent inhibitory properties. In vitro assays were employed to conduct qualitative phytochemical analyses and to quantify total phenolic content, total flavonoid content, and α-glucosidase enzyme activity. The results demonstrate that high salinity stress enhances the inhibitory activity of mulberry leaf extracts against the α-glucosidase enzyme. Notably, the MB2-3 sample exhibited the most favorable IC50 value (0.59 µg/mL), coupled with a substantial phenolic content (141.9 mg GAE/g extract) and the highest content of flavonoid observed among all tested samples (619.56 mg QE/g extract). Collectively, these findings highlight the capacity of salinity stress to augment both the inhibitory potential of mulberry extracts against α-glucosidase and the accumulation of phenolic and flavonoid compounds, with sample MB2-3 displaying auspicious attributes.